Circadian system coordination: new perspectives beyond classical models - Baltatu, Ovidiu Constantin; Campos, Luciana Aparecida; Cipolla-Neto, José (Frontiers in Physiology, 2025)
BackgroundThis review examines novel interaction mechanisms contributing to the robustness of circadian rhythms, focusing on enhanced communication between the suprachiasmatic nucleus (SCN) and peripheral clocks. While classical models explain biological clocks through molecular interactions and biochemical signaling, they incompletely account for several key features: precision maintenance despite cellular noise, rapid system-wide synchronization, and temperature compensation. We propose that the SCN, acting as a central hub, may utilize non-classical mechanisms to maintain robust synchronization of peripheral clocks, contributing to biological timekeeping stability. The clinical implications of this model are significant, potentially offering new approaches for treating circadian-related disorders through quantum-based interventions. Recent advances in quantum biosensors and diagnostic tools show promise for early detection and monitoring of circadian disruptions, while quantum-based therapeutic strategies may provide novel treatments for conditions ranging from sleep disorders to metabolic syndromes.Aim of reviewTo evaluate classical models of circadian rhythm robustness and propose a novel synchronization model incorporating quantum mechanical principles, supported by recent advances in quantum biology and chronobiology, with emphasis on potential clinical applications.Key scientific conceptsRecent research in quantum biology suggests potential mechanisms for enhanced circadian system coordination. The proposed model explores how quantum effects, including entanglement and coherence, may facilitate rapid system-wide synchronization and temporal coherence across tissues. These mechanisms could explain features not fully addressed by classical models: precision maintenance in noisy cellular environments, rapid resynchronization following environmental changes, temperature compensation of circadian periods, and sensitivity to weak electromagnetic fields. The framework integrates established chronobiology with quantum biological principles to explain system-wide temporal coordination and suggests new therapeutic approaches for circadian-related disorders.